Evaluation of solvent system for the enzymatic synthesis of ethanol-based biodiesel from sludge palm oil (SPO) - Nasaruddin, Ricca Rahman; Alam, Md Zahangir; Jami, Mohammed Saedi (Elsevier, 2014)
A green technology of biodiesel production focuses on the use of enzymes as the catalyst. In enzymatic biodiesel synthesis, suitable solvent system is very essential to reduce the inhibition effects of the solvent to the enzymes. This study produced ethanol-based biodiesel from a low-cost sludge palm oil (SPO) using locally-produced Candida cylindracea lipase from fermentation of palm oil mill effluent (POME) based medium. The optimum levels of ethanol-to-SPO molar ratio and enzyme loading were found to be 4:1 and 10 U/25 g of SPO respectively with 54.4% w/w SPO yield of biodiesel and 21.7% conversion of free fatty acid (FFA) into biodiesel. Addition of tert-butanol at 2:1 tert-butanol-to-SPO molar ratio into the ethanol–solvent system increased the yield of biodiesel to 71.6% w/w SPO and conversion of FFA into biodiesel to 28.8%. The SPO and ethanol have promising potential for the production of renewable biodiesel using enzymatic-catalyzed esterification and transesterification.